2020
DOI: 10.1108/tqm-05-2020-0110
|View full text |Cite
|
Sign up to set email alerts
|

Development of an integrated framework of LGSS strategies for Indian manufacturing firms to improve business performance: an empirical study

Abstract: PurposeThis article aims to explore synergies between Lean, Green and Six Sigma practices in order to propose an integrated LGSS framework for continuous and incremental improvement in the Indian manufacturing industries. The three-dimensional LGSS framework seeks to provide various combinations and support operational, financial, environmental and social needs.Design/methodology/approachIn the research method, first, the current problems faced by Indian manufacturing industries are considered and proposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 111 publications
0
23
0
1
Order By: Relevance
“…Together, Green and Lean can identify waste and evaluate its environmental effect but they often do not provide an actual method/ technique to reduce waste (Garza-Reyes, 2015b). However, Six Sigma has the potential to fill up the gap by providing a methodology for process improvement (Garza-Reyes, 2015a; Gaikwad and Sunnapwar, 2020b). Moreover, according to Garza-Reyes (2015a), Lean Green and Six Sigma are complementary; therefore, each paradigm has the potential to minimize the disadvantage of each other.…”
Section: Integrated Lgandss Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, Green and Lean can identify waste and evaluate its environmental effect but they often do not provide an actual method/ technique to reduce waste (Garza-Reyes, 2015b). However, Six Sigma has the potential to fill up the gap by providing a methodology for process improvement (Garza-Reyes, 2015a; Gaikwad and Sunnapwar, 2020b). Moreover, according to Garza-Reyes (2015a), Lean Green and Six Sigma are complementary; therefore, each paradigm has the potential to minimize the disadvantage of each other.…”
Section: Integrated Lgandss Approachmentioning
confidence: 99%
“…Moreover, according to Garza-Reyes (2015a), Lean Green and Six Sigma are complementary; therefore, each paradigm has the potential to minimize the disadvantage of each other. Integrated LG&SS practices provide a systematic and holistic approach to problem-solving through incremental enhancement in manufacturing sectors (Gaikwad and Sunnapwar, 2020b). Integrated LG&SS strategies help manufacturing sector to compete in the global markets by adopting sustainability strategy in their business (Gaikwad and Sunnapwar, 2020a).…”
Section: Integrated Lgandss Approachmentioning
confidence: 99%
“…Now, industries facing power shortages become a significant problem. SLM considers as strong management and manufacturing strategy for continuous improvement (Womack et al , 1990; Gaikwad and Sunnapwar, 2020). Now, researchers have analyzed further tools and techniques and its impact on operational, environmental and economic performance by elimination of waste, which impact product cost, quality and lifecycle (Negrao et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that the interest and scope of implementation of integrated lean-green manufacturing system increased surprisingly as both approaches lead to reduction in waste and product cost by continuously improving the quality of products and processes (Prasad et al, 2016;Chugani et al, 2017;Govindan et al, 2015;Oliveira et al, 2018;Gupta et al, 2018). For instance, Gaikwad and Sunnapwar (2020) explored synergies between Lean, Green and Six Sigma (LGSS) practices and proposed a three dimensional LGSS framework for continuous and incremental improvement in the manufacturing industries. The result of the study suggested that there is a positive impact of integrated practices on firm performance in terms of operational, financial, social and environmental outcomes.…”
Section: Introductionmentioning
confidence: 99%